Blockchain technology and its roles in the accounting system / Raziah Bi Mohamed Sadique, Salwa Muda and Musliha Musman - Mohamed Sadique, Raziah Bi; Muda, Salwa; Musman, Musliha (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Blockchain, a revolutionary technology, is not just a digital ledger. It's a decentralized and distributed system that ensures data integrity and transparency. Unlike traditional databases, blockchain operates through a network of nodes, each with a complete copy of the ledger, decentralizing control. This unique structure allows participants to directly verify transactions without intermediaries, enhancing transparency and trust. Transactions are organized into blocks, linked chronologically to form a chain, with each block containing multiple transactions added in a linear order. Consensus mechanisms like Proof of Work (PoW) or Proof of Stake (PoS) validate transactions, fortifying the blockchain's security and tamper-resistant nature. Transactions on the blockchain are transparent to all participants, enhancing accountability. While data may be encrypted or anonymized, the transaction records remain public, fostering trust within the network. Blockchain employs cryptographic techniques to secure data, with each block linked to the previous one through a cryptographic hash, preserving the integrity of the entire chain. Once a block is added, altering it necessitates consensus among most of the network, making the blockchain resistant to unauthorized modifications.